Guidance for addressing gaps in information and uncertainty in activity data for livestock greenhouse gas emissions: Uruguay - From reporting 12 NGHGI to UNFCCC to a key policy tool - Oyhantçabal, Walter (2018)
Expert workshop on Improving activity data for Tier 2 estimates of livestock emissions: Dealing with data gaps The Hauge, July 17-18, 2018 Uruguay experience